The effects of Autumn foliar spray of urea on the productivity and quality of apple Golden delicious and Starking delicious cultivars fruits in the condition of Dahr al- Qusair region/ Hamah (Damascus University Journal of agriculture sciences, 2021)
The research was carried out during the period (2015-2017) in an apple field in Burshin village/ Hama governorate, which planted with the tow cultivars 'Golden delicious' and 'Starking delicious' grafted on seedlings (Malus domestica), in order to demonstrate the effect of urea sprays in the Autumn with concentration (5%, 7.5%, 10%) in the tree productivity of two studied cultivars and some qualitative properties of fruits. The study showed that concentration of 10% urea caused injuries to apple leaves for both cultivars during a week from spraying urea, the results also showed that there were not significant effect of two concentration 5%, and 7.5% on the shoot length, and the quality of the fruits comparing with the control, and there were also no significant differences in term of trees productivity comparing with the control, the average of productivity for the cultivar "Golden delicious" ranged from 72.52 to 80.45 kg/tree in the first season and from 90.98 to 99.69 kg/tree in the second one, for "Starking delicious" cultivar the average of productivity ranged from 42.33 to 48 kg/tree in the first season and from 59.25 to 64 kg/tree for the second one. The application of urea foliar spray in the Autumn, with concentration of (5, 7.5%) had no significant effect on the average of fruit hardness at harvest time, and on the total soluble solids ratio compared to the control in both seasons and in both cultivars “Golden Delicious” and “Starking Delicious”.
Keywords: Autumn foliar spray; Urea; Apple